What drives negative investment-cash flow sensitivities? Revenue effect versus corporate life-cycle dynamics - Jochen Lawrenz; Julia Oberndorfer (Schmalenbach Journal of Business Research (SBUR), 2023)
In order to identify the economic driver of negative investment-cash flow sensitivities (ICFS), we derive testable predictions from extending a theoretical investment model with endogenous financing costs ("revenue effect") and contrast them with the corporate life-cycle hypothesis. We find that firms with (i) lower levels of long-term debt display stronger negative ICFS, and (ii) firms with more risky revenues invest more, which contradicts the predictions of the revenue effect. At the same time firms with strongly negative ICFS are (iii) smaller, (iv) younger and (v) have higher growth opportunities, which is consistent with the life-cycle hypothesis.
Keywords: G31; G32; 650; Corporate Life-Cycle; Cost-Revenue Effect; Investment-Cash Flow Sensitivity; Nonlinearities